Mechanical Circulatory Support for Myocarditis Complicated by Cardiogenic Shock - Jankuvienė, Agnė; Ščupakova, Nadežda; Urbonas, Karolis; Mikelevič, Lilė; Drutel, Renata; Samalavičius, Robertas (Lietuvos chirurgija, 2021)
Background. Cardiogenic shock caries high mortality and morbidity. Myocarditis patients developing cardiogenic shock refractory to medical treatment might benefit from extracorporeal membrane oxygenation or mechanical ventricular assist devices. Methods. A retrospective, single center observational study to assess the rate and outcomes of mechanical circulatory support of patients with fulminant myocarditis related cardiogenic shock. Short-term outcomes were evaluated. The primary endpoint of the study was hospital survival. Results. Two hundred ninetyone patient were supported with short-term mechanical assist devices at our institution during 12 year period. Among them, 4 (1.4%) were treated for myocarditis related cardiogenic shock. All patients were female, with a mean age of 34±4 years. In one case surgically implantable short-term mechanical assist device was used, in other three cases – extracorporeal membrane oxygenation. The mean duration of the support was 364±273 hours, mean intensive care unit stay – 35±29 days. Three of four patients were successfully weaned from the support and discharged from the hospital with complete heart function recovery. Conclusion. Patient with fulminant myocarditis, who would have died without the initiation of mechanical circulatory, had favorable short-term outcome with 75% survival rate.
Keywords: mechanical circulatory support; ECMO; cardiogenic shock; survival